خصوصية التحكيم الالكتروني في حل منازعات التجارة الالكترونية The Privacy Of Arbitration In Resolving Conflicts Of Electronic Commerce - بن حليمة, ليلى; عشور, سليم (Université de M'sila, 2019)
إن خصوصية وطبيعة العقود الالكترونية التي تبرم في إطار شبكة الانترنت تجعل منها عقودا غير مرتبطة بالحيز المكاني، مما يثير صعوبة تحديد القانون الواجب التطبيق عليها، وعليه فقد تم استحداث آلية جديدة للفصل في المنازعات التي قد تنشأ عنها، من خلال اللجوء إلى التحكيم الالكتروني الذي يسمح للأطراف باستخدام التقنيات الالكترونية في عقد جلسات التحكيم وصدور الحكم وتنفيذه. The privacy of the nature of the electronic contracts concluded in the framework of the network of the Internet makes it contracts not related to office space, which raises the difficulty of determining the applicable law, therefore, the introduction of a new mechanism to settle the disputes that may arise, through recourse to arbitration email, which allows the parties to use the electronic techniques in the meetings of the arbitral tribunal and the judgment and implementation.
Keywords: التحكيم الالكتروني، حل منازعات التجارة الالكترونية، خصوصية. ; Electronic Arbitration, Resolving conflicts of electronic commerce, privacy.